Mixed‐methods evaluation of a multifaceted heart failure intervention in general practice: the OSCAR‐HF pilot study. (3rd December 2022) - Smeets, Miek; Raat, Willem; Aertgeerts, Bert; Penders, Joris; Vercammen, Jan; Droogne, Walter; Mullens, Wilfried; Janssens, Stefan; Vaes, Bert
Abstract: Aims: Heart failure (HF) is an important health problem for which multidisciplinary care is recommended, yet few studies involve primary care practitioners in the multidisciplinary management of HF. We set up a multifaceted prospective observational trial, OSCAR‐HF, piloting audit and feedback, natriuretic peptide testing at the point of care, and the assistance of a specialist HF nurse in primary care. The aim was to optimize HF care in general practice. Methods and results: This is an analysis at 6 month follow‐up of the study interventions of the OSCAR‐HF pilot study, a nonrandomized, noncontrolled prospective observational trial conducted in eight Belgian general practices [51 general practitioners (GPs)]. Patients who were assessed by their GP to have HF constituted the OSCAR‐HF study population. We used descriptive statistics and mixed‐effects modelling for the quantitative analysis and thematic analysis of the focus group interviews. There was a 10.2% increase in the registered HF population after 6 months of follow‐up ( n  = 593) compared with baseline ( n  = 538) and a 27% increase in objectified HF diagnoses (baseline n  = 359 to 456 at T6 M). Natriuretic peptide testing (with or without referral) accounted for 54% ( n  = 60/111) of the newly registered HF diagnoses. There was no difference in the proportion of patients with HF with reduced ejection fraction who received their target dosage of renin‐angiotensin‐aldosterone system inhibitors or beta‐blockers at 6 months compared with baseline ( P  = 0.9). Patients who received an HF nurse intervention ( n  = 53) had significantly worse quality of life at baseline [difference in Minnesota Living with Heart Failure Questionnaire (MLHFQ) score 9.2 points; 95% confidence interval (CI) 4.0, 14] and had a significantly greater improvement in quality‐of‐life scores at the 6 month follow‐up [change in MLHFQ score −9.8 points; 95% CI −15, −4.5] than patients without an HF nurse intervention. GPs found audit and feedback valuable but time intensive. Natriuretic peptides were useful, but the point‐of‐care test was impractical, and the assistance of an HF nurse was a useful addition to routine HF care. Conclusions: The use of audit and feedback combined with natriuretic peptide testing was a successful strategy to increase the number of registered and objectified HF diagnoses at 6 months. GPs and HF nurses selected patients with worse quality‐of‐life scores at baseline for the HF nurse intervention, which led to a significantly greater improvement in quality‐of‐life scores at the 6 month follow‐up compared with patients without an HF nurse intervention. The interventions were deemed feasible and useful by the participating GPs with some specific remarks that can be used for optimization. Trial Registration: ClinicalTrials.gov (NCT02905786), registered on 14 September 2016 at https://clinicaltrials.gov/ .